PERSPEKTIF PSIKOLOGI DALAM KOMUNIKASI LINTAS BUDAYA - Lis Yulianti Syafrida Siregar (Universitas Islam Negeri (UIN) Mataram, 2015)
This paper discusses about psychology on perspective intercultural communication. Cultural varieties areinfluenced by many factors, including differences in perception. It is undeniable that perception gives influence to the culture, attitude, and behavior. Perception in this time is a big factor on communication because communication influences social culture. Then difference of communication isa part of intercultural communication.